2016
DOI: 10.1111/juaf.12258
|View full text |Cite
|
Sign up to set email alerts
|

Foreclosures, Investors, and Uneven Development during the Great Recession in the Los Angeles Metropolitan Area

Abstract: In the wake of the U.S. housing crisis, what has happened to the substantial stock of foreclosed or real estate–owned (REO) properties is only beginning to be understood. The eventual outcomes of these properties are central to our understanding of the varied impacts of the foreclosure crisis, including its contribution to enduring and emerging patterns of uneven development. This article considers the scope and potential impacts of investor purchases of foreclosures in diverse neighborhoods in the Los Angeles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 38 publications
2
15
0
1
Order By: Relevance
“…For example, Gilderbloom and colleagues (2012) found that investor activity played an important role in determining neighborhood-level exposure to foreclosure and abandonment. Likewise, investors have played a significant role in the acquisition of foreclosed, single-family properties, particularly in poor and predominantly non-white neighborhoods (Immergluck and Law 2014b; Molina 2016).…”
Section: The Sociology Of Housing Disinvestmentmentioning
confidence: 99%
“…For example, Gilderbloom and colleagues (2012) found that investor activity played an important role in determining neighborhood-level exposure to foreclosure and abandonment. Likewise, investors have played a significant role in the acquisition of foreclosed, single-family properties, particularly in poor and predominantly non-white neighborhoods (Immergluck and Law 2014b; Molina 2016).…”
Section: The Sociology Of Housing Disinvestmentmentioning
confidence: 99%
“…Once again the fastest-growing spatial form in the United States, exurbia outpaces urban, rural, and suburban growth (Frey, 2015), becoming home not only to an exurbanite asset class but also to poor and working people who service them (Berube et al., 2006; Taylor, 2011). Since the 2008 recession, exurbia is not generally absorbing major institutional capital investment—cities assumed that role—but exurbs are the destination of popular capital investment, namely through individual homebuyers, who in the aggregate comprise a major capital flow (Molina, 2015). This popular capital makes the politics of exurban places increasingly consequential to the US political economy more broadly.…”
Section: Resultsmentioning
confidence: 99%
“…Pfeiffer and Lucio (2015), for example, contrast mom-and-pop investors with large corporations and Wall Street firms like the Blackstone Group and Colony Capital. In the foreclosure crisis in California in the United States related to the GFC, Molina (2016) found that between 2007 and 2010, mom-and-pop investors frequently seized the opportunity to enter property markets alongside larger corporate investors. Similar dynamics have been observed in Phoenix, Arizona, where mom-and-pop operations played a crucial role in the conversion of single-family homes into rental properties (Immergluck and Law 2014).…”
Section: Size and Social Compositionmentioning
confidence: 99%